FILSAFAT TAUHID DALAM LANDASAN EKONOMI SYARIAH MENGHADAPI FINTECH DAN KECERDASAN BUATAN (AI) - Venotty Ananda Putri; Hermawan Maulana; Muhammad Rifky Azis; Meiska Amelia; Balqis Nadya Shafwa (Taksasila Edukasi Insani, 2026)
This study aims to strengthen and continuing previous studies on Islamic economic philosophy by emphasizing the central role of the philosophy of monotheism (Tauhid) as the fundamental basis for sustainable sharia economic development in the future, especially in the face of Financial Technology (Fintech) and Artificial Intelligence (AI). Unlike previous studies that mainly focused on normative and institutional aspects, this research focuses on integrating the values of monotheism across all epistemological, ontological, and axiological dimensions of Islamic economics to overcome contemporary digital challenges such as cybersecurity risks, data breaches, and algorithmic bias. Through careful literature review and content analysis, the study concludes that the principle of monotheism is not only a theological foundation but also an ethical and rational guide for utilizing digital technology. These guidelines must be based on the values of justice (Al-Adl), balance (Tawazun), public welfare (Maslahah), and harmony with the principles of Maqashid Syariah. Therefore, this study is expected to provide a new direction for building a sustainable Sharia economy and preserving Islamic values in the digital age.Keywords : Fintech, Islamic Economics, Maqasid al-Sharia, Tawhid Philosophy